Pembuatan Engine Stand Suzuki ST 100 Sebagai Media Pembelajaran di Bengkel Otomotif Politeknik Negeri Ujung Pandang - Ari, A. Ariputra; Wahyuni, Nur; Arfandi, Arfandi; Maulana Ilmunandar, Alief; Rahmatullah, Rahmatullah; Lora, Sudirman (Jurnal Teknik Mesin Sinergi, 2025)
Engine stand is an iron frame used as an engine mount. The working principle of an engine stand is to facilitate engine maintenance and repairs. Based on a case study conducted by the researcher, it was found that Politeknik Negeri Ujung Pandang Automotive Workshop did not yet have an engine stand, especially for the Suzuki ST 100 engine. This is also an obstacle when students carry out maintenance and repair practicums. The purpose of this study is to make it easier for students to carry out maintenance and repairs on the engine, so that the Suzuki ST 100 can be operated again as a learning medium for practicums. The place where the Engine Stand was made was at the Ujung Pandang State Polytechnic Automotive Workshop which was carried out from May to August 2024. The method in this study was to assemble the components on the frame, then install the engine on the engine stand that had been made, then overhaul the engine to ensure that the engine could work properly. The test results obtained were that all components could function normally again and the engine stand was safe to use because the strength of the engine stand frame to withstand an engine load of 90 kg, there was no change either bent or broken. The conclusion of this study is that the engine stand can be used as a strong engine mount and the Suzuki ST 100 engine can run normally after making several repairs and replacing its components.